SIKAP BURUH TANI DI KECAMATAN PGL BDG MENGHADAPI ANJURAN STAY AT HOME - Deni Sutisna; Arif Widodo; Muhammad Sobri; Mohammad Archi Maulyda; Nursaptini Nursaptini (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2020)
This study aims to examine the problems of various community behaviors in facing the threat of COVID-19, especially of farmworkers on the PGL sub-district, Bdg district. The basic reason for this research is that in the midst of the government's great efforts to suppress the spread of this virus by limiting community activities, both social distancing and suggestions to stay at home in various areas, the people of PGL sub-district, especially farmers and farm laborers, are still carrying out their activities. like before the COVID-19 pandemic. The descriptive method is used in this research. Observations were made with interview techniques and documentation because they were very appropriate for studying descriptive social problems such as this research. The reasons for farmers and farm laborers to continue their activities are: First, farm workers in PGL think that the COVID-19 pandemic will not hit their area, they believe they will remain healthy because of their work patterns that are outdoors and exposed to direct sunlight. The two economic factors and difficulties in fulfilling the necessities of life, the third is the lack of public awareness farmworkers about the dangers of COVID-19. Penelitian ini bertujuan untuk mengaji permasalahan tentang berbagai perilaku masyarakat dalam menghadapi ancaman COVID-19 terutama masyarakat kalangan buruh tani yang berada di kawasan kecamatan PGL kabupaten Bdg. Alasan mendasar dari penelitian ini adalah di tengah usaha pemerintah yang begitu besar dalam upaya menekan penyebaran virus ini dengan membatasi aktivitas masyarakat baik social distancing ataupun anjuran untuk stay at home di berbagai wilayah, tetapi masyarakat kecamatan PGL khususnya pada kalangan petani dan buruh tani masih menjalankan aktivitasnya seperti sebelum terjadi pandemi COVID-19. Metode deskriptif digunakan dalam penelitian ini. Pengamatan dilakukan dengan teknik wawancara, dan dokumentasi karena sangat tepat untuk mengkaji permasalahan sosial yang bersifat deskripsi seperti penelitian ini. Alasan para buruh tani tetap beraktivitas adalah: Pertama, buruh tani di PGL beranggapan pandemik COVID-19 tidak akan melanda wilayahnya, mereka berkeyakinan tetap sehat karena pola kerja mereka yang berada di luar ruangan dan terkena sinar matahari langsung. Kedua, faktor ekonomi dan kesulitan dalam pemenuhan kebutuhan hidup; ketiga, kurangnya kesadaran masyarakat kalangan buruh tani akan bahaya dari COVID-19.